117k views
3 votes
Show me how you solve it

Show me how you solve it-example-1

1 Answer

5 votes

Answer:

5^20

Explanation:

Law of Exponent I


\displaystyle \large{ \frac{ {a}^(m) }{ {a}^(n) } = {a}^(m - n) }

Therefore:


\displaystyle \large{( \frac{ {5}^(8) }{ {5}^(3) } )^(4) = ({5}^(8 - 3))^(4) } \\ \displaystyle \large{( \frac{ {5}^(8) }{ {5}^(3) } )^(4) = ({5}^(5))^(4) }

Law of Exponent II


\displaystyle \large{( {a}^(m) ) ^(n) = {a}^(m * n) }

Thus:


\displaystyle \large{( \frac{ {5}^(8) }{ {5}^(3) } )^(4) = ({5}^(8 - 3))^(4) } \\ \displaystyle \large{( \frac{ {5}^(8) }{ {5}^(3) } )^(4) = ({5}^(5))^(4) } \\ \displaystyle \large{( \frac{ {5}^(8) }{ {5}^(3) } )^(4) = {5}^(5 * 4) } \\ \displaystyle \large{( \frac{ {5}^(8) }{ {5}^(3) } )^(4) = {5}^(20) }

Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.